Prediagnostic serum glyceraldehyde‐derived advanced glycation end products and mortality among colorectal cancer patients. Issue 11 (20th March 2023) - Mao, Ziling; Baker, Jacqueline Roshelli; Takeuchi, Masayoshi; Hyogo, Hideyuki; Tjønneland, Anne; Eriksen, Anne Kirstine; Severi, Gianluca; Rothwell, Joseph; Laouali, Nasser; Katzke, Verena; Kaaks, Rudolf; Schulze, Matthias B.; et al.
Abstract: Glyceraldehyde‐derived advanced glycation end products (glycer‐AGEs) could contribute to colorectal cancer development and progression due to their pro‐oxidative and pro‐inflammatory properties. However, the association of glycer‐AGEs with mortality after colorectal cancer diagnosis has not been previously investigated. Circulating glycer‐AGEs were measured by competitive ELISA. Multivariable Cox proportional hazards models were used to calculate hazard ratios (HRs) and corresponding 95% confidence intervals (CIs) for associations of circulating glycer‐AGEs concentrations with CRC‐specific and all‐cause mortality among 1034 colorectal cancer (CRC) cases identified within the European Prospective Investigation into Cancer and Nutrition (EPIC) study between 1993 and 2013. During a mean of 48 months of follow‐up, 529 participants died (409 from CRC). Glycer‐AGEs were statistically significantly positively associated with CRC‐specific (HRQ5 vs Q1  = 1.53, 95% CI: 1.04‐2.25, P trend  = .002) and all‐cause (HRQ5 vs Q1  = 1.62, 95% CI: 1.16‐2.26, P trend  < .001) mortality among individuals with CRC. There was suggestion of a stronger association between glycer‐AGEs and CRC‐specific mortality among patients with distal colon cancer (per SD increment: HRproximal colon  = 1.02, 95% CI: 0.74‐1.42; HRdistal colon  = 1.51, 95% CI: 1.20‐1.91; P effect modification  = .02). The highest HR was observed among CRC cases in the highest body mass index (BMI) and glycer‐AGEs category relative to lowest BMI and glycer‐AGEs category for both CRC‐specific (HR = 1.78, 95% CI: 1.02‐3.01) and all‐cause mortality (HR = 2.15, 95% CI: 1.33‐3.47), although no statistically significant effect modification was observed. Our study found that prediagnostic circulating glycer‐AGEs are positively associated with CRC‐specific and all‐cause mortality among individuals with CRC. Further investigations in other populations and stratifying by tumor location and BMI are warranted. Abstract : What's new? Eating foods high in sugar has been associated with risk of colorectal cancer (CRC). As the body processes dietary sugars, it generates compounds called glyceraldehyde‐derived advanced glycation end products (glycer‐AGEs). Here, the authors investigated the relationship between glycer‐AGEs and CRC mortality. In an analysis of 1034 CRC cases from the EPIC cohort, they found that prediagnostic circulating glycer‐AGEs were associated with both CRC‐specific and all‐cause mortality.